Autism And Its Treatment In Malaysia : Holistic Care for Autistic Children - See, Ching Mey (2005)
Three different ministries in Malaysia provide services for autistic children in specific and children with special nedds in general. They are the Ministry of Education; Ministry of Health; and Ministry of Women, Family & Community Development particulary Social Welfare Department. In addition to these, Non-Government Agencies (NGOs) also play an important role in providing services for these children.